Bibliometric Trends in Diatom Research: Emphasis on Lakes and Oxbow Lakes Ecosystems - Sofia Puspitarini; Tri Retnaningsih Soeprobowati; Lilih Khotimperwati; Jumari Jumari; Mirza Hanif Al Falah; Yustiawati Yustiawati; Ardianor Ardianor; Łukasz Kruszewski (BRIN Publishing, 2025)
Diatoms are unicellular microalgae that play a vital role in freshwater ecosystems and are widely recognized as effective bioindicators of aquatic environmental conditions. This paper presents a literature review and bibliometric analysis of the composition and distribution of diatoms in lakes, focusing on oxbow lakes. Bibliometric data were retrieved from the Scopus database and analyzed using the R software with the Bibliometrix package. The results revealed a rising trend in publications over the past two decades, especially concerning climate change, habitat degradation, and environmental monitoring. The Journal of Paleolimnology and researchers such as John P. Smol have emerged as a leading contributors in terms of publication volume and scientific impact. Furthermore, oxbow lakes remain underexplored despite their ecological importance, indicating significant opportunities for future research. This study emphasizes the need for interdisciplinary approaches to support sustainable conservation and management of freshwater ecosystems.